Penerapan Prinsip Tanggung Jawab dan Sanksi Pidana dalam Hukum Kesehatan terhadap Peredaran Kosmetik Ilegal - Kartiko, Nafis Dwi; Soegiono, Samuel Putra; Indradewi, Astrid Athina; Ginting, Yuni Priskila; Boong, Vicariya Retnowati (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This research aims to conduct a juridical analysis of cases of circulation of illegal cosmetic products. The method used is normative-dogmatic juridical research, which focuses on relevant legal doctrines and principles. The approach used is a conceptual approach and a statutory approach, with primary legal sources including the Health Law, BPOM Regulations, the Criminal Code (KUHP), and the Criminal Procedure Code (KUHAP). Secondary legal sources include journals, books, and other references that support the analysis. The results show that the distribution of illegal cosmetic products that do not meet safety and quality standards, as in the case of the defendant Megawati binti Rahmat alias Mega in verdict number 39/Pid.Sus/2020/PN Slr, is a serious violation of health law and consumer protection in Indonesia. Based on the principle of liability based on the element of fault, the defendant can be held legally responsible because it is proven that she distributed cosmetics without a distribution permit containing hazardous substances such as mercury. The Panel of Judges considered that the defendant's actions fulfilled the elements of unlawful acts in accordance with Article 1365 of the Civil Code and Article 196 of Law of the Republic of Indonesia Number 36 of 2009 concerning Health. The implications of this research emphasize the importance of strict law enforcement and the application of the principle of responsibility to protect public health from dangerous cosmetic products.